Analysis of the impact of personal selling, promotion, and brand image on the purchase decision of Mitsubishi cars at PT Dipo International Pahala Otomotif - Vigo, Marvin; Harvin, Frans; Ciawi, Natalia; Chandria, Vivi; Saribu, Holfian Daulat Tambun; Hutauruk, Rapat Piter Sony (Priviet Social Sciences Journal, 2023)
This research aims to examine the influence of personal selling, promotion, and brand image on the purchase decision of Mitsubishi cars at PT Dipo International Pahala Otomotif. The declining phenomenon in purchase decisions is evident from the decrease in the number of units sold. Personal selling is currently focused only on exhibitions in shopping centers, thus not operating optimally. The promotions tend to rely more on discounts and less varied trade promotions, providing limited choices for consumers. The well-known brand image of Mitsubishi, perceived positively by consumers for its quality, is acknowledged. The research methodology employs quantitative research with data analysis using descriptive methods. The population in this study consists of 128 customers at PT Dipo International Pahala Otomotif, with a sample determined through simple random sampling, totaling 97 customers. The conclusions drawn from the research indicate that, both partially and simultaneously, personal selling, promotion, and brand image have a positive and significant impact on purchase decisions, with a coefficient of determination of 93.8%.